A leadership framework for distributed self-organized scrum teams. Issue 5 (15th August 2017) - Srivastava, Pallavi; Jain, Shilpi
Abstract : Purpose: Scrum, an agile software development method, has gained major interest among software development organizations. The scrum master should be well equipped with specific leadership traits and exhibit leadership behavior to effectively manage his/her team. However, in a distributed team, which is spread across geographies, having scrum master to lead the project team at each location is not viable. Therefore, every member in the team is expected to have the capability to become one. This paper aims to explore the leadership mechanisms desired for effective functioning of distributed self-organized scrum team members, leading to project success and overall customer satisfaction. Design/methodology/approach: A qualitative research methodology with an open-ended questionnaire is followed by semi-structured in-depth interviews. The unit of analysis is a scrum master. Findings: The qualitative findings unearth the kind of leadership mechanisms required for scrum masters and the team members in a self-organizing scrum team, leading to their project success and customer satisfaction. It includes a set of leadership approaches and behaviors explicitly related to the role of scrum masters. Both inductive and deductive approaches are used to develop a leadership framework applicable for distributed self-organized scrum teams. Research limitations/implications: The proposed framework can be empirically tested with a large number of teams and more software organizations. Practical implications: Organizations can use these identified specific leadership approaches and behaviors as parameters for identifying and selecting the potential scrum masters. They can be further trained on them to be an effective scrum master. Originality/value: There is scant literature on the leadership mechanisms necessary for distributed scrum teams and their impact on project performance. This paper addresses this gap.